2020
DOI: 10.3390/foods9030291
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds in Food Waste: A Review on the Transformation of Food Waste to Animal Feed

Abstract: Bioactive compounds are substances which are present in foods in small amounts and have the ability to provide health benefits. Bioactive compounds include but are not limited to long-chain polyunsaturated fatty acids, vitamins, carotenoids, peptides, and polyphenols. The aim of the present study is to review literature for potential bioactive compounds present in food waste material and discuss the transformation of food waste to animal feed under the perspective that usage of food waste, rather than disposal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
57
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(76 citation statements)
references
References 55 publications
1
57
1
Order By: Relevance
“…In the European Union, the Waste Framework Directive 2008/98/EC proposed the following waste management hierarchy: prevention, processing for reuse, recycling, energy recovery and disposal [ 4 ]. In this scenario, several authors [ 5 , 6 , 7 ] have suggested that the use of less food-competing foodstuffs in animal diets is a potential strategy for reducing food–feed competition and mitigating the environmental impact of livestock. This approach is particularly pertinent when coupled with other strategies such as improvements in livestock productivity [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the European Union, the Waste Framework Directive 2008/98/EC proposed the following waste management hierarchy: prevention, processing for reuse, recycling, energy recovery and disposal [ 4 ]. In this scenario, several authors [ 5 , 6 , 7 ] have suggested that the use of less food-competing foodstuffs in animal diets is a potential strategy for reducing food–feed competition and mitigating the environmental impact of livestock. This approach is particularly pertinent when coupled with other strategies such as improvements in livestock productivity [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, the pharmaceutical industry has become aware that the bio-waste originating from grapes and apples processing can be an important source of phytochemicals to be destined to cosmetic, pharmaceutical and food industries [ 1 , 6 , 7 , 8 , 9 ]. As a consequence, bio-waste has being recently used for the production of dietary supplements, functional foods, food additives and nutraceuticals for human consumption [ 4 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…One way of addressing this impeding issue has been identified as “recycling”. As such, several processes have been explored worldwide in order to effectively reuse various by-products [ 4 , 5 ]. In this context, food waste could be regarded as alternative sources used in animal nutrition, diminishing food competition between humans and animals [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…As such, several processes have been explored worldwide in order to effectively reuse various by-products [ 4 , 5 ]. In this context, food waste could be regarded as alternative sources used in animal nutrition, diminishing food competition between humans and animals [ 5 ]. Recent scientific advancement has been focused on characterizing various agricultural by-products for further utilization as animal feed, including potential effects on health and animal performance [ 6 ].…”
Section: Introductionmentioning
confidence: 99%